Development of sustainable ulva lactuca genus algae and hemp based composites for agrotextiles application - UZUN, MUHAMMET (My University, 2023)
As the global population grows, there is an increasing demand for food, requiring sustainable farming methods to increase agricultural productivity. Soil covers and mulches used in agriculture are mostly made of synthetic materials derived from petrochemicals, which pose various problems such as soil contamination and long-term insolubility. This study aims to use Ulva Lactuca algae as a sustainable raw material for soil covers, as it contains vitamins and minerals that the soil needs. As seawater acidity increases, the population of this algae is also increasing, creating the opportunity to use it in agriculture. The product is expected to retain moisture and reduce water consumption and high temperatures. In addition, hurds obtained from industrial hemp waste are used due to their high-water retention potential. The study combined Ulva lactuca algae from the Marmara region and hemp strings from Narlı and Vezir seeds to create various composites with different structures. Basic tests were conducted to determine the mechanical and physical properties of the products. The goal is to increase soil organic matter by using these materials as fertilizer after their use as soil covers.
Keywords: Ulva Lactuca; Algae; Hemp; Biodegradable Agrotextiles; Sustainability